2020
DOI: 10.1186/s40985-020-00141-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of behavioural interventions targeting hand hygiene practices among nurses in high-income hospital settings: a systematic review

Abstract: Background Hand hygiene is a critical behaviour for infection control but efforts to raise compliance among clinical professionals have been met with mixed success. The aim of this systematic review was to identify the effectiveness of the behaviour change techniques utilised in recent hand hygiene interventions that seek to improve hand hygiene compliance among nurses in hospitals in high-income countries. Nurses are at the frontline of healthcare delivery, and so improving their HH behaviour and thus increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Feedback on behaviour has previously been shown as a significantly encouraging technique for changing long‐term antibiotic prescribing behaviour (Crayton et al, 2020). Findings from a systematic review of behavioural interventions to changing hand hygiene amongst nurses found that goals and planning, feedback and monitoring, and comparison of behaviour were most commonly used to change behaviour (Sands et al, 2020). Participants could be encouraged to think about their current AMS‐related behaviours and future solutions, we recommend 6.2 social comparison of behaviour , more frequent use of 1.1 goal setting , and techniques to review 1.6 discrepancy between current behaviour and these goals.…”
Section: Discussionmentioning
confidence: 99%
“…Feedback on behaviour has previously been shown as a significantly encouraging technique for changing long‐term antibiotic prescribing behaviour (Crayton et al, 2020). Findings from a systematic review of behavioural interventions to changing hand hygiene amongst nurses found that goals and planning, feedback and monitoring, and comparison of behaviour were most commonly used to change behaviour (Sands et al, 2020). Participants could be encouraged to think about their current AMS‐related behaviours and future solutions, we recommend 6.2 social comparison of behaviour , more frequent use of 1.1 goal setting , and techniques to review 1.6 discrepancy between current behaviour and these goals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review examining behavioural interventions to improve hand hygiene has noted a change in emphasis from direct measures such as providing alcohol hand-rub towards more motivational techniques. These include goal setting and planning, comparing individual and group behaviour, and provision of feedback (Sands et al 2020). It may be that newer educational interventions are making a similar move from didactic teaching to a more reflective approach.…”
Section: Discussionmentioning
confidence: 99%
“…When considering educational interventions it is important to consider cognitive learning, psychomotor, and affective skills (World Health Organization 2009); and to work towards including the higher levels of a taxonomy such as that by Bloom which deal with synthesis and analysis; as well as the lower levels of knowledge, comprehension and application (Adams 2015). However, as with the behavioural change interventions, unpicking and identifying each of these in an individual educational intervention which forms part of a broader educational programme can be challenging (Sands et al 2020). A more reflective approach might also elevate patient safety to the same level as that of personal protection, which may for some be a more compelling force for change (Borg et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…5 Multifaceted behavior change-oriented interventions have effectively promoted hand hygiene compliance and subsequent reduction of nosocomial infection in health care settings. 6,7 Clinical research assistants (RAs) frequently work alongside clinical staff and interact with patients but may be excluded from infection control training programs and may receive no formal instruction on hand hygiene procedures. As a result, existing hand hygiene data audits carried out by health authorities may be inaccurate estimates of true adherence to hand hygiene by all hospital personnel in the patient environment and may not reflect true healthcare-associated infection transmission pediatric emergency department (ED) and subsequently increase group hand hygiene adherence to 80% over 11 months through evidence-based interventions.…”
Section: Introductionmentioning
confidence: 99%
“…5 Multifaceted behavior change-oriented interventions have effectively promoted hand hygiene compliance and subsequent reduction of nosocomial infection in health care settings. 6,7…”
Section: Introductionmentioning
confidence: 99%